Will Job Crafters Stay or Leave? The Roles of Organizational Instrumentality and Inclusive Leadership - Xin, Xun; Cai, Wenjing; Gao, Xueyuan; Liu, Tingting (Frontiers in Psychology, 2021)
Although studies have indicated the influences of job crafting on contemporary employees’ working outcomes, the path from job crafting to turnover intention is still unexplored in depth. Drawing on goal facilitation theory, we delineate how job crafting relates to turnover intention through organizational instrumentality, and conditioned by inclusive leadership. We collected data from 218 employees from Chinese high-tech companies at two different time points via submitting survey questionnaires. Results indicate that employees’ job crafting relates positively to their perception of organizational instrumentality, and further results in decreased turnover intention. We also find that inclusive leadership not only positively moderates the path from job crafting to organizational instrumentality, but also positively moderates the whole mediational relationship. Moreover, job crafting relates positively and directly to turnover intention—i.e., the more employees craft their jobs, the more likely they leave their organizations when we control the roles of organizational instrumentality and inclusive leadership. Finally, the theoretical and practical implications are also discussed.